Enabling Delay Tolerance in IoT based Vehicular Networks - Sharma, Aditya; Maan, Akash (International Journal of Scientific Research in Computer Science and Engineering, 2022)
The essence of IoT devices in the networks involving the management of Smart Traffic can be seen in urban cities. The optimal movement of the vehicles, pollution monitoring and control, efficient utilization of the resources, and ensuring security while vehicular communications are some of the key issues related to Smart Traffic Management. This paper aims to keep track of the current Delay Tolerant Network (DTN) application in IoT based Vehicular Networks. Vehicular Delay Tolerant Network (VDTN) is one of the most important IoT applications. Delay Tolerant Networks (DTNs) are introduced to reduce latency and to counter the data loss and data theft conditions that were present in Wireless Ad Hoc networks (WANET). Connectivity, transmission, and security issues in Wireless Ad Hoc networks if used in Vehicular Networks can result in serious losses as the presence of small loopholes in the network can lead to major accidents. This paper aims to provide general insights into the DTN architecture and routing protocols. Applications of Delay Tolerant Network in Vehicular networks as Vehicular Delay Tolerant Networks (VDTNs) along with the routing issues and challenges related to the VDTNs are also presented as a part of this comprehensive work.